MAIN CHARACTERISTICS OF THE SKIN DERMIS - qizi, Shavkatxonova Marjona Fayzullo (Journal of Medical Genetics and Clinical Biology, 2024)
General Background: The dermis, the skin's second layer, plays a crucial role in skin health and functionality. Positioned beneath the epidermis, it serves as a structural support for the skin. Specific Background: Comprised primarily of connective tissue, the dermis is rich in proteins such as collagen and elastin, which are essential for maintaining skin integrity and elasticity. Knowledge Gap: Despite the recognized importance of the dermis in dermatological health, detailed understanding of its composition and the role of the extracellular matrix (ECM) in skin aging and disease is limited. Aims: This study aims to elucidate the main characteristics of the dermis, focusing on its structural components and their contributions to skin health. Results: The findings highlight the predominance of collagen and elastin as the primary structural proteins, alongside the crucial role of hyaluronic acid in the ECM, which maintains hydration and resilience of the dermal layer. Novelty: This research offers new insights into the interplay between dermal components and skin aging, suggesting that a better understanding of these elements may inform therapeutic strategies for skin rejuvenation and disease management. Implications: The implications of this study extend to clinical practices, emphasizing the need for targeted interventions that enhance dermal health, thereby contributing to improved aesthetic and functional outcomes in dermatology. This knowledge could pave the way for innovative treatments aimed at preserving skin youth and preventing age-related skin disorders.